2010
DOI: 10.3892/ijmm_00000532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MammaPrint and TargetPrint results with clinical parameters in German patients with early stage breast cancer

Abstract: Abstract. The 70-gene expression profile MammaPrint is a powerful prognostic indicator for disease outcome in breast cancer patients with improved prediction of recurrence risk compared to currently used guidelines. The microarraybased test TargetPrint further provides reliable, quantitative assessment of mRNA expression levels of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). This study was performed as a validation of MammaPrint and TargetPrint in an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(34 reference statements)
2
18
0
1
Order By: Relevance
“…The methodological quality of the seven included studies 75,[92][93][94]96,99,100 is summarised in Figure 4 (further details are provided in Appendix 9). Generally, only two studies 75,93 performed well, receiving a positive assessment for at least 17 out of 21 methodological quality items.…”
Section: Quality Of Included Studies: Mammaprintmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodological quality of the seven included studies 75,[92][93][94]96,99,100 is summarised in Figure 4 (further details are provided in Appendix 9). Generally, only two studies 75,93 performed well, receiving a positive assessment for at least 17 out of 21 methodological quality items.…”
Section: Quality Of Included Studies: Mammaprintmentioning
confidence: 99%
“…A German-based study 95 investigating 140 majority LN-and ER+ patients was reported by Gevensleben et al 94 The authors made a comparison between risk prediction using the 70-gene prognostic signature and risk prediction using the St Gallen criteria 95 and Adjuvant! Online (Adjuvant!…”
Section: Buenomentioning
confidence: 99%
See 1 more Smart Citation
“…Among the participants who were recommended to receive adjuvant therapy after consideration of clinical guidelines, patient preference, and prognosis signature, 18, 29, and 13% of participants were recommended for chemotherapy alone, chemotherapy plus hormone therapy, and hormone therapy only, respectively. One additional study summarized by Ward et al 40 retrospectively compared actual treatment received with participants’ MammaPrint risk classifications. Among 59 participants classified as high risk, 19 (32%) did not receive chemotherapy, whereas 35 out of 77 participants classified as low risk did receive chemotherapy.…”
Section: Evidence Overviewmentioning
confidence: 99%
“…It was suggested that MammaPrint would affect the treatment 40% of the time based on the assumption that all high-risk participants would receive chemotherapy and all low-risk participants would not. 40 Heterogeneity in the study populations and in the initial criteria used to make treatment decisions limits the ability to generalize the impact of MammaPrint on clinical decision making. Indirectness in the interpretation of results, participant characteristics, and the lack of a reliable control groups led us to determine there is low-quality evidence for MammaPrint to lead to change in treatment decisions or recommendations ( Table 3 ).…”
Section: Evidence Overviewmentioning
confidence: 99%